Reversible Solid-to-Liquid Phase Transition of Coordination Polymer Crystals - Umeyama, Daiki; Horike, Satoshi; Inukai, Munehiro; Itakura, Tomoya; Kitagawa, Susumu (Journal of the American Chemical Society, 2015)
The solid-to-liquid phase transition, a fundamental process commonly observed for various types of substances with significant potential for application, has been given little attention in the field of coordination polymers (CPs) despite the rich functionality of these compounds. In this article, we report the reversible solid-to-liquid phase transition of crystalline CPs. These CPs are composed of zinc ions, phosphate, and azoles, and a well-balanced composition, ionicity, and bond strength afford “melting” CPs. We examined the structure of one such melting framework in the liquid and glass states and found that the coordination bonds are not fully preserved in the liquid state but are re-formed in the glass state. As a demonstration, we fabricated, via phase transition, a thin film with an aligned crystal orientation and a monolith crystal of the CP.